Spread of injectate with superficial cervical plexus block in humans: an anatomical study. - Pandit, J; Dutta, D; Morris, J (2003)
BACKGROUND: This study was undertaken to investigate why the superficial cervical plexus block for carotid endarterectomy is so effective. Initial consideration would suggest that a superficial injection would be unlikely to block all terminal fibres of relevant nerves. One possibility is that the local anaesthetic crosses the deep cervical fascia and blocks the cervical nerves at their roots. METHODS: Superficial cervical plexus blocks (injections just below the investing fascia) were performed using methylene blue (30 ml) in four cadavers. In one additional control cadaver, a deep cervical plexus injection was performed. In a second control cadaver, a subcutaneous injection (superficial to investing fascia) was performed at the posterior border of the sternomastoid muscle. RESULTS: Anatomical dissection showed that with superficial block there was spread of the dye to structures beneath the deep cervical fascia. In the first control, dye remained in the deep cervical space. In the second control, dye remained subcutaneous. CONCLUSIONS: The superficial cervical space communicates with the deep cervical space and this may explain the efficacy of the superficial block. The method of communication remains unknown. Our findings also indicate that the suitable site of injection for the superficial cervical plexus block is below the investing fascia of the neck, and not just subcutaneous.